Ferroportin 1 depletion in neural stem cells promotes hippocampal neurogenesis and cognitive function in mice - Yiqian Ding; Shanshan Yao; Shuxin Guo; Wei Meng; Jie Li; Fudi Wang; Jianhua Zhang; Yan-Zhong Chang; Guofen Gao (Pharmacological Research)
In the adult brain, newborn granule cells continuously integrate into the hippocampal circuits, and fine-tuning the regulation of this process is crucial for improving hippocampal function. Iron is an essential element for the development and functionality of the brain. Ferroportin 1 (Fpn1) is an iron efflux transporter that plays a crucial role in regulating cellular iron release. In this study, Nestin-CreERT2-mediated Fpn1 conditional knockout (cKO) mice were established to investigate the impact of Fpn1 depletion in neural stem cells (NSCs) on adult hippocampal neurogenesis. Interestingly, we found that the cKO mice presented better learning and memory abilities and fewer anxiety-like behaviors. The numbers of self-renewing NSCs and NSCs undergoing proliferation and differentiation were significantly increased in the hippocampus of Fpn1 cKO mice, resulting in greater numbers of newborn neurons than in control mice. Further investigation revealed that the elevated iron levels in NSCs and iron-mediated increase in ROS generation in Fpn1 cKO mice contributed to the enhanced hippocampal neurogenesis through PI3K/Akt and MAPK signaling activation. Notably, iron supplementation promoted the proliferation of primary NSCs dose-dependently, whereas the presence of ROS inhibitor abolished this effect. This study reveals that Fpn1 of NSCs and its regulated iron levels are key modulators of hippocampal neurogenesis through promoting the proliferation of NSCs and ultimately controlling hippocampal function. These findings may provide valuable insights into stem cell-targeting treatments for neurological diseases.